Maternal outcomes among pregnant women with shunt-related congenital heart disease-associated pulmonary hypertension: a retrospective study - Tiantian Sun; Hao Che; Jun Zhang; Yufang Lv; Yaguang Liu; Daqi Liu; Jinjing Wu; Sheng Wang; Liyun Zhao (BMC Anesthesiology)
Abstract Background Studies on pregnant women with shunt-related congenital heart disease (CHD)-associated pulmonary hypertension (PH) are scarce and limited by small sample sizes. This study aimed to describe the outcomes of pregnant women. Methods Outcomes of pregnant women with shunt-related CHD-associated PH were retrospectively evaluated from 2010 to 2020. PH was diagnosed based on echocardiography. The incidence of maternal death and postoperative vasoactive drug therapy were compared between women with mild-to-moderate and severe PH. The characteristics and factors influencing postoperative vasoactive drug therapy in women with severe PH were studied. Postoperative vasoactive drug therapy was defined as the use of vasoactive drugs for over 48 h after cesarean section or abortion to maintain circulatory stability. Results A total of 255 pregnant patients with shunt-related CHD-associated PH were enrolled, including 147 with mild-to-moderate pulmonary artery systolic pressure (PASP) of 30–70 mmHg and 108 with severe PH (PASP > 70 mmHg). Overall, women with mild-to-moderate PH had better maternal outcomes than those with severe PH, including the incidence of maternal mortality (0.68% vs. 11.11%, P < 0.001) and postoperative vasoactive drug therapy (2.74% vs. 50.47%, P < 0.001). Gestational week at delivery (OR 0.9, 95% CI[0.82,0.98], P = 0.016), Eisenmenger syndrome (OR 2.64, 95% [1.08,6.64], P = 0.034), and New York Heart Association (NYHA) functional class III to IV (OR 5.22, 95% [1.90,14.35], P < 0.001) were independently associated with postoperative vasoactive drug therapy in pregnant women with severe PH. Conclusions Women with shunt-related CHD-associated mild to moderate PH had better outcomes than those with severe PH in terms of the incidence of maternal mortality and postoperative vasoactive drug therapy. Multimodal risk assessment, including PH severity, gestational week, Eisenmenger syndrome, and NYHA functional class, may be useful for risk stratification in pregnant women with shunt-related CHD-associated PH.